EFFECT OF CATTLE MANURE AND LOF DERIVED FROM CHICKEN EGGSHELLS ON THE GROWTH AND YIELD OF SHALLOT (Allium cepa L.): PENGARUH PUPUK KANDANG SAPI DAN POC CANGKANG TELUR AYAM TERHADAP PERTUMBUHAN DAN HASILBAWANG MERAH (Allium cepa L.) - Vita Erlita; M. Yusuf; Septiariani Zuliati (ROCE : Jurnal Pertanian Terapan, 2026)
Shallots (Allium cepa L.) are a horticultural commodity with high economic value and widespread consumption. This study aimed to evaluate the effect of cow manure and liquid organic fertilizer (LOF) made from chicken eggshells on the growth and yield of shallots. The study was conducted at the experimental garden and Plant Physiology Laboratory, Faculty of Agriculture, Malikussaleh University, from November 2024 to February 2025. The experiment was arranged using a two-factorial Randomized Block Design (RBD) with three replications. The first factor was the dose of cow manure (0, 40, and 80 g polybag⁻¹), while the second factor was the concentration of chicken eggshell POC (0, 50, and 100 mL L⁻¹ water). The results showed that cow manure significantly affected plant height at 2 weeks after planting (WAP), root weight and volume, fresh and dry tuber weight per clump, and yield, with the best response at a dose of 40 g polybag⁻¹. Chicken eggshell LOF significantly affected plant height at 4 weeks post-plant growth (WAP), root length and volume, root weight, fresh and dry tuber weight, and yield, with the highest value at a concentration of 100 mL L⁻¹ of water. The interaction of the two treatments significantly affected root weight and volume, with the best combination at a dose of 80 g cow manure per polybag⁻¹. The combination of cow manure and chicken eggshell POC has been shown to increase shallot growth and yield.